Gallic acid‐based alkyl esters synthesis in a water‐free system by celite‐bound lipase of Bacillus licheniformis SCD11501. (18th March 2015) - Sharma, Shivika; Kanwar, Shamsher S.; Dogra, Priyanka; Chauhan, Ghanshyam S.
<x xml:space="preserve">Abstract</x> Gallic acid (3, 4, 5‐ trihydroxybenzoic acid) is an important antioxidant, anti‐inflammatory, and radical scavenging agent. In the present study, a purified thermo‐tolerant extra‐cellular lipase of Bacillus licheniformis SCD11501 was successfully immobilized by adsorption on Celite 545 gel matrix followed by treatment with a cross‐linking agent, glutaraldehyde. The celite‐bound lipase treated with glutaraldehyde showed 94.8% binding/retention of enzyme activity (36 U/g; specific activity 16.8 U/g matrix; relative increase in enzyme activity 64.7%) while untreated matrix resulted in 88.1% binding/retention (28.0 U/g matrix; specific activity 8.5 U/g matrix) of lipase. The celite‐bound lipase was successfully used to synthesis methyl gallate (58.2%), ethyl gallate (66.9%), n‐propyl gallate (72.1%), and n‐butyl gallate (63.8%) at 55oC in 10 h under shaking (150 g) in a water‐free system by sequentially optimizing various reaction parameters. The low conversion of more polar alcohols such as methanol and ethanol into their respective gallate esters might be due to the ability of these alcohols to severely remove water from the protein hydration shell, leading to enzyme inactivation. Molecular sieves added to the reaction mixture resulted in enhanced yield of the alkyl ester(s). The characterization of synthesised esters was done through fourier transform infrared (FTIR) spectroscopy and 1H NMR spectrum analysis. © 2015 American Institute of Chemical Engineers Biotechnol. Prog., 31:715–723, 2015